COMPARING ANALYSIS OF PRETREATMENT METHODS OF WOOD AND BONE MATERIALS FOR THE CHRONOLOGY OF PERIPHERAL BURIALS AT TUNNUG 1, TUVA REPUBLIC, RUSSIA. Issue 1 (1st February 2022) - Pawełczyk, Fatima; Hajdas, Irka; Sadykov, Timur; Blochin, Jegor; Caspari, Gino
ABSTRACT: Nine burials from Tunnug 1 site in Tuva Republic, which contained human and animal bones as well as remains of wood, were chosen for intercomparison study of preparation methods. Nine human bones, nine animal bones and 11 pieces of wood were prepared. Gelatin extracted from bones was purified using the UF method but the extraction from bones was modified with respect to acid and base treatment. Wood samples were treated as whole using acid-base-acid and cellulose was extracted for comparison. The results confirmed a highly consistent chronology of the sites centered at 200–400 CE, however, a few bones resulted in an offset between ages obtained by different methods. The extraction of cellulose was limited due to the poor preservation of wood. Our results highlight problems of dating poorly preserved bones and wood.